Pengembangan Media Pembelajaran Interaktif Matematika Berbasis Web Articulate Storyline untuk Meningkatkan Minat Belajar Siswa SMP - Messa Dwi Rahmania; Abdul Fatah; Nurul Anriani (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2023)
The minimal use of learning media and less attractive conventional methods harm students' interest in mathematics. Therefore, researchers developed interactive learning media based on WEB Articulate Storyline to stimulate students' interest in learning mathematics. This study uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) developmental research model. Observation, questionnaires, and documentation are the data collection techniques used. Quantitative descriptive analysis is the data analysis technique used. The study results show that the developed learning media is highly valid, as evident from the assessment results by subject matter experts, obtaining an average percentage of 90%, and media experts, obtaining an average percentage of 96.25%. Additionally, the developed media has proven to be very practical, based on the assessment results by teachers, obtaining an average percentage of 91.67%, and student assessments, obtaining an average percentage of 84.95%. Articulate Storyline media has been proven effective in increasing students' interest in learning, as seen from the N-Gain test results obtaining a value of 0.651, which falls into the moderate category. Based on the results of this study, the developed Articulate Storyline learning media is highly appropriate and practical for implementation in mathematics education. It effectively enhances students' interest in learning mathematics.